PROTAGONISMO JUVENIL E GRÊMIO ESTUDANTIL: A PRODUÇÃO DO INDIVÍDUO RESILIENTE - Jorge Luis Cammarano González; Marcilene Rosa Leandro Moura (EccoS – Revista Científica)
This writing investigates and inquires about the role of Union Student, at ambit of teaching state education of Sorocaba city, understood as one of the instances that derivates social practices with the aim of individual formation. This analysis circumscribes itself to: (1) the origin and to the historic expressions of secondary students movement and (2) the understanding of reformist strategy, specifically at scholar education, materialized by Brazilian state since the nineties. Based upon those aspects, it tries to understand if the human being, specifically the Student Union, would materialize and transform a social movement tendentiously and predominantly in a space mediated by assistance practices, politicized of action of their subjects, on the adaptation perspective to the social reality in a course converting to the formation of resilient social being.